Research on the impact of digital inclusive finance on rural human capital accumulation: A case study of China - Li, Hanjin; Zhuge, Ruiyang; Han, Jin; Zhao, Peng; Gong, Maogang (Frontiers in Environmental Science, 2022)
Affordability, accessibility, and easiness of digital financial inclusion has gained great attention from scholars in past few years. However, they ignore the effect of digital financial inclusion on backward regions. Besides, it does not even highlighted who will enjoy the benefits of digital inclusion or which section of the economy remains deprived or unaware. Although, human capital has become a mean of efficiency, growth, and a key factor for attaining sustainability, specifically via premises of digitization. Hence, in this study, researcher tries to disclose the effect of digital financial inclusion on human capital accumulation in rural China. For the economy of China, it was proven that there is ‘digital divide’ that is similar to ‘educational divide’ which is occurring due to less available facilities, poor infrastructure, financial literacy, increasing urbanization, and low income levels. Therefore, this paper tries to explore the long run cointegration between rural human capital and digital inclusive finance by incorporating three major dimensions of digital finance that are breadth of coverage, degree of digitalization, and the depth of use. For empirical examination, 31 provinces of China has been selected over the time 2011-2020 and the targeted audience here is socially disadvantaged people belonging to Eastern, Central, Western and northeast China. Inflation, state financial expenses on education, urbanization, disposable income, and degree of state openness has been taken as independent variable while, human capital accumulation is employed as a dependent variable. Generalized Method of Movement (GMM)/dynamic panel regression has been utilized which revealed that digital inclusive finance significantly contributes rural human capital accumulation. A regional analysis has also been performed to check individual contribution of each region. Conversely, regional estimates disclosed that digital finance inclusion in Eastern, Central, and Western region provokes more static and significant effect on rural human capital accumulation than in Northeast China. Researcher suggest introduction of sound and static policies in Northeast China for promoting digital financial inclusion that in turn accumulate rural human capital.